Existence of infinitely many small solutions for a class of fractional Schrodinger-Poisson systems (Nonlinear Studies, 2022)
We consider a fractional Schrodinger-Poisson system with a sublinear nonlinearity and general potential. Applying a new symmetric Mountain Pass Theorem established by Kajikia, we prove the existence of infinitelymany small solutions for this system. Some examples are also given to illustrate our main theoretical result.